Oscillation rheometry of curing process of epoxy binders modified with polyetherimide - S. V. Polunin; K. A. Atamas; I. Yu. Gorbunova; P. A. Morozova; K. M. Marakhovsky (Тонкие химические технологии, 2025)
Objectives. The aim of this study is to ascertain the influence of polyetherimide on the curing process of epoxy binders.Methods. The storage modulus and loss modulus of epoxyamine systems were measured as a function of curing time on the Anton Paar MCR 302 rheometer. The experiments were carried out at an oscillation frequency of 1 Hz, with an amplitude aligned with the linear viscoelasticity region, and across a range of temperatures (160, 170, and 180°C). The crossover point was determined when the components of the complex modulus of elasticity are equal according to the obtained dependencies.Results. The influence of polyetherimide on the curing process of epoxyamine binders was investigated at a thermoplastic content of 5 to 20 pts. wt at three temperatures. In a system modified with 20 pts. wt of polyetherimide, phase separation was observed during the curing process. In systems modified with 10 and 20 pts. wt of polyetherimide, the limiting value of the modulus of elasticity was observed to be higher at 170°C than at 180°C.Conclusions. The modification of epoxyamine binders with thermoplastic in an amount of 5–20 pts. wt has been observed to extend the time required to reach the crossover point. Furthermore, the curing process markedly slows down in the system comprising 10 pts. wt of thermoplastic content, in which it takes the longest time to reach the crossover point at all three experimental temperatures.